Landscape, Place and Culture : Linkages between Australia and India. - Bandyopadhyay, Deb (Cambridge Scholars Pub., 2011)
This collection of essays takes an interdisciplinary approach to the ecological, social, economic and, in particular, the cultural dimensions of the Australia-India relationship. The essays provide many levels of focus on environment, place and culture. Some evoke appreciation of particular "places," either in India or Australia. Many explore how literature has treated "landscape," while some are comparative studies of cultural, historical and political development. The essays arise from a p ...